Characterization of Pebax angioplasty balloon surfaces with AFM, SEM, TEM, and SAXS. Issue 3 (17th April 2015) - Warner, Jacob A.; Forsyth, Bruce; Zhou, Fang; Myers, Jason; Frethem, Chris; Haugstad, Greg
Abstract: In the medical device industry, angioplasty balloons have been widely used in the less invasive treatment of heart disease by expanding and relieving clogged structures in various arterial segments. However, new applications using thin coatings on the balloon surface have been explored to enhance therapeutic value in the delivery of pharmaceuticals (drug‐elution) or control thermal energy output (RF ablation). In this study, angioplasty balloon materials comprised of poly(ether‐ block ‐amide) (Pebax) were investigated via atomic force microscopy (AFM), transmission electron microscopy (TEM), scanning electron microscopy (SEM), and small‐angle X‐ray scattering (SAXS) to characterize physical properties at the balloon surface that may affect coating adhesion. The soft segment of this Pebax 1074 material is polyethylene oxide (PEO) and the hard segment is nylon‐12. The morphology of the hard segments of this block co‐polymer are found via AFM stiffness measurements to be (40 ± 20) nm by (300 ± 150) nm and are oriented parallel to the surface of the balloon. SAXS measurements found the lamellar spacing to be (18.5 ± 0.5) nm, and demonstrate a preferential orientation in agreement with TEM and AFM measurements. Fixation of this balloon in resin, followed by cryo‐sectioning is shown to provide a novel manner in which to investigate surface characteristics on the balloon such as material or coating thickness as well as uniformity in comparison to the bulk structure. These outputs were deemed critical to improve overall balloon processing such as molding and surface treatment options for robust designs toward better procedural outcomes targeting new therapeutic areas. © 2015 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 104B: 470–475, 2016.